2018
DOI: 10.1002/nur.21875
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy and cultural analysis of intra‐hospital patient transfers

Abstract: Existing research on intra-hospital patient transitions focuses chiefly on handoffs, or exchanges of information, between clinicians. Less is known about patient transfers within hospitals, which include but extend beyond the exchange of information. Using participant observations and interviews at a 1,541-bed, academic, tertiary medical center, we explored the ways in which staff define and understand patient transfers between units. We conducted observations of staff (n = 16) working in four hospital departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 32 publications
5
36
0
2
Order By: Relevance
“…It has been suggested that handoffs should be studied at the minimum by unit type (Rikos, Linardakis, Economou, Rovithis, & Philalithis, 2019; Staggers & Blaz, 2013). Differences exist between unit cultures and job requirements (Rosenberg et al., 2018). For instance, the handoff is considered especially important and more challenging in the ICU, because of the critical nature of the patient's condition and inherent complexity thereof (Colvin, Eisen, & Gong, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that handoffs should be studied at the minimum by unit type (Rikos, Linardakis, Economou, Rovithis, & Philalithis, 2019; Staggers & Blaz, 2013). Differences exist between unit cultures and job requirements (Rosenberg et al., 2018). For instance, the handoff is considered especially important and more challenging in the ICU, because of the critical nature of the patient's condition and inherent complexity thereof (Colvin, Eisen, & Gong, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…ED nursing staff are likely to use various handoff strategies to compensate for their challenging environment (Venkatesh, Curley, Chang, & Liu, 2015). General ward nursing staff typically take care of less severely ill patients and see themselves as mainly providing patient‐centred care (Rosenberg et al., 2018). In this study, the unit‐specific results indicate that the surgery wards demonstrated the most significant improvement in information transfer.…”
Section: Discussionmentioning
confidence: 99%
“…While it is critical to understand the risks posed to patients during transfers, the impact of transfers on hospital staff from a wide array of professional backgrounds is less well-understood (Halvorson et al, 2016;Rosenberg et al, 2018). Research that acknowledges staff experiences in maintaining patient safety during intra-hospital transfers is needed to understand other factors that contribute to adverse events, delays in care and other risks to patients (Hearld, Alexander, Fraser, & Jiang, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Research that acknowledges staff experiences in maintaining patient safety during intra‐hospital transfers is needed to understand other factors that contribute to adverse events, delays in care and other risks to patients (Hearld, Alexander, Fraser, & Jiang, ). To this end, a quality improvement project using an ethnographic approach was conducted to examine the latent conditions that affected how multidisciplinary team members experienced intra‐hospital transfers from the Emergency Department and Medical Intensive Care Unit to General Internal Medicine floors at an urban teaching hospital (Rosenberg et al, ). Observations of and interviews with team members including clinicians (nurses, physicians and a physician's assistant) and support staff (unit clerks and bed managers and bed associates who assigned patients to beds) informed the development of a taxonomy of intra‐hospital transfers (Rosenberg et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation